Randomized Controlled Trial of E-Counseling for Hypertension: REACH. Issue 7 (July 2018) - Nolan, Robert P.; Feldman, Ross; Dawes, Martin; Kaczorowski, Janusz; Lynn, Hazel; Barr, Susan I.; MacPhail, Carolyn; Thomas, Scott; Goodman, Jack; Eysenbach, Gunther; Liu, Sam; Tanaka, Rika; et al.
Abstract : Background: The efficacy of internet-based interventions to improve hypertension management is not established. We evaluated the therapeutic benefit of e-counseling by adapting best evidence guidelines for behavioral counseling. Methods and Results: This multicenter double-blind randomized controlled trial included assessments at baseline, 4 months, and 12 months. Participants were 35 to 74 years of age and diagnosed with hypertension: systolic/diastolic blood pressure (BP) 130 to 180/85 to 110 mm Hg. BP was assessed by automated office measurement. E-Counseling used multimedia and interactive tools to increase motivation and skill for self-care (exercise, diet, medication adherence, and smoking cessation). Control used self-care education. Frequency of contact by our e-platform was equal for both trial arms. Primary end points were change at 4 and 12 months in systolic BP, diastolic BP, pulse pressure, total lipoprotein cholesterol, low-density lipoprotein cholesterol, total lipoprotein cholesterol/high-density lipoprotein cholesterol ratio, non–high-density lipoprotein cholesterol, and Framingham 10-year cardiovascular risk index. Intention-to-treat analysis used generalized linear models adjusted for baseline measures, sex, and medications. Among 264 participants, mean age was 57.6 years (SE, 0.6), 58% were women, with 83% on antihypertensive medications. At 12 months, e-counseling versus control evoked greater reduction in systolic BP (−10.1 mm Hg [95% confidence interval (CI), −12.5, −7.6] versus −6.0 mm Hg [95% CI, −8.5, −3.5]; P =0.02); pulse pressure (−5.2 mm Hg [95% CI, −6.9, −3.5] versus −2.7 mm Hg [95% CI, −4.5, −0.9]; P =0.04), and Framingham risk index (−1.9% [95% CI, −3.3, −0.5] versus −0.02% [95% CI, −1.2, 1.7]; P =0.02), respectively. Among males in e-counseling versus control, 12-month end points included lower diastolic BP ( P =0.01), non–high-density lipoprotein cholesterol ( P =0.04), total lipoprotein cholesterol ( P =0.03), and a trend for total lipoprotein cholesterol/high-density lipoprotein cholesterol ratio ( P =0.07). Conclusions: To our knowledge, this is the first double-blind randomized trial of e-counseling for hypertension. Added benefit for medical therapy was achieved by combining available technology with a clinically organized protocol of motivational and cognitive-behavioral counseling. Clinical Trial Registration: https://www.clinicaltrials.gov ; Unique identifier: NCT01541540 Abstract : Supplemental Digital Content is available in the text.